Better to trust in the lord?: religious salience, regime religiosity, and interstate dispute resolution - Zellman, Ariel (Journal of global security studies, 2024)
How do religiously salient issues influence the peaceful resolution of interstate territorial disputes? Conflict scholars tend to represent “religious” disputes as uniquely resistant to compromise owing to their supposed symbolic indivisibility and the ideological inflexibility of the actors who pursue them. Rather, we argue that religious regimes’ preferred forums to advance peaceful resolution depend upon interactions between the breadth of a dispute’s religious salience and a claimant regime’s domestic religious legitimacy. Secular regimes lack both religious legitimacy and political motivation to engage. Thus, their dispute resolution forum preferences are unrelated to religious salience. Highly religious regimes command significant religious legitimacy and are therefore empowered to directly negotiate over broadly salient religious issues. Yet their political dependence upon religious constituencies causes them to strictly avoid legally binding conflict management over narrowly salient religious issues. By contrast, moderately religious regimes lack sufficient religious legitimacy to directly negotiate over both broadly and narrowly salient issues, rendering them particularly dispute-resolution avoidant. We test and generally confirm these propositions, utilizing new data measuring the religious salience of interstate territorial disputes in the post-Cold War era.